Light-induced responses of slow oscillatory neurons of the rat olivary pretectal nucleus. - Hanna J Szkudlarek (Public Library of Science (PLoS), 2012)
Background The olivary pretectal nucleus (OPN) is a small midbrain structure responsible for pupil constriction in response to eye illumination. Previous electrophysiological studies have shown that OPN neurons code light intensity levels and therefore are called luminance detectors. Recently, we described an additional population of OPN neurons, characterized by a slow rhythmic pattern of action potentials in light-on conditions. Rhythmic patterns generated by these cells last for a period of approximately 2 minutes. Methodology To answer whether oscillatory OPN cells are light responsive and whether oscillatory activity depends on retinal afferents, we performed in vivo electrophysiology experiments on urethane anaesthetized Wistar rats. Extracellular recordings were combined with changes in light conditions (light-dark-light transitions), brief light stimulations of the contralateral eye (diverse illuminances) or intraocular injections of tetrodotoxin (TTX). Conclusions We found that oscillatory neurons were able to fire rhythmically in darkness and were responsive to eye illumination in a manner resembling that of luminance detectors. Their firing rate increased together with the strength of the light stimulation. In addition, during the train of light pulses, we observed two profiles of responses: oscillation-preserving and oscillation-disrupting, which occurred during low- and high-illuminance stimuli presentation respectively. Moreover, we have shown that contralateral retina inactivation eliminated oscillation and significantly reduced the firing rate of oscillatory cells. These results suggest that contralateral retinal innervation is crucial for the generation of an oscillatory pattern in addition to its role in driving responses to visual stimuli.